1992
DOI: 10.1177/027112149201200207
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attitudes Toward Integration

Abstract: Recent studies concerning parental attitudes toward preschool mainstreaming indicate a favorable disposition toward this arrangement by parents of typical children and those of children with disabilities in mainstreamed settings. This study seeks to replicate and extend these findings. Discussed are the first-year results of a 5-year longitudinal study of parental attitudes toward mainstreaming in school-age programs. Surveyed were 230 parents. Results indicated that the parents, regardless of their child's pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 9 publications
3
27
0
1
Order By: Relevance
“…These parents may also harbor concerns regarding their children's safety; the attitudes of other students, staff and program quality; and transportation (Hanline & Halvorsen, 1989). However, parent engagement and partnership can lead to increased acceptance of disability, improved learning, and better classroom behaviors (Edutopia, 2000), and research has shown that, as inclusive education systems become more established, parents adopt a decisively positive view of inclusive education (Miller & Phillips, 1992). Additionally, evidence suggests that increased parent engagement and partnership in the special education process leads to improved learning outcomes for students with disabilities (Stoner et al, 2005).…”
Section: Parentsmentioning
confidence: 99%
“…These parents may also harbor concerns regarding their children's safety; the attitudes of other students, staff and program quality; and transportation (Hanline & Halvorsen, 1989). However, parent engagement and partnership can lead to increased acceptance of disability, improved learning, and better classroom behaviors (Edutopia, 2000), and research has shown that, as inclusive education systems become more established, parents adopt a decisively positive view of inclusive education (Miller & Phillips, 1992). Additionally, evidence suggests that increased parent engagement and partnership in the special education process leads to improved learning outcomes for students with disabilities (Stoner et al, 2005).…”
Section: Parentsmentioning
confidence: 99%
“…The IITDC and IICD scales were based on items from the Parental Attitudes toward Mainstreaming Scale (Green & Stoneman, 1989) and the Benefits and Drawbacks of Mainstreaming Scale (Bailey & Winton, 1987). The Parents Attitudes toward Inclusion/Integration, 13-questions scale was created by Rafferty, Boettcher and Griffin (2001) and based on items from the Attitudes about Integration Opportunities for Children with Special Needs by Miller, Strain, Boyd, Hunsicker, McKinley and Wu (1992).…”
Section: Instrumentationmentioning
confidence: 99%
“…Understanding the perceptions of parents whose children attend inclusive programs is vital for the ultimate success of the inclusion philosophy (Erwin, Soodak, Winton & Turnbull, 2001;Garrick-Duhaney, & Salend, 2000). Generally, parents of preschool children with and without disabilities have positive perceptions concerning inclusion (Miller & Strain, 1992;Bennett, Deluca, & Bruns, 1997;Rafferty & Griffin, 2005). Parents sited an increased awareness and acceptance of children with disabilities, teacher-child ratios and extra services as positive components of the inclusive educational setting (Bailey & Winton, 1987;Guralnick, 1994).…”
mentioning
confidence: 99%
“…Improvement in the quality of childcare for all children, and particularly young children with disabilities, is another concern (Daniels, 1996). Many parents would prefer to place their children in a childcare setting that provides developmental support as well as a stimulating and responsive environment (Miller et al, 1993). The reality for many families, however, especially for families of young children with special needs, is that they are unable to find safe and affordable childcare programs that address basic childcare issues of safety, engagement, and affection.…”
Section: Challenges To Inclusion In Community-based Programsmentioning
confidence: 99%